Associated Gas Utilization in Libya: Challenges, Opportunities, and Sustainable Development (مجلة الفاروق للعلوم, 2026)
Gas flaring remains a critical environmental and economic challenge in global oil production, with Libya ranking among the top flaring nations worldwide. Despite holding Africa’s largest proved oil reserves and significant natural gas resources, Libya flared approximately 6.3 billion cubic meters of associated gas in 2024, resulting in an estimated economic loss of $650 million. This study provides a comprehensive analysis of associated gas utilization in Libya, exploring the technical, economic, and regulatory barriers that perpetuate routine flaring. Through an examination of recent policy developments, including Libya's 2026 endorsement of the World Bank's "Zero Routine Flaring by 2030" initiative and the National Oil Corporation's pledge to reduce flaring by 83%, this paper identifies strategic pathways for gas monetization. Technologies such as gas-to-power, liquefied natural gas (LNG), and reinjection for enhanced oil recovery are evaluated within the Libyan context. The findings demonstrate that capturing and utilizing associated gas can significantly enhance domestic energy security, boost export revenues, and align the nation with global climate mitigation goals. The paper concludes with actionable policy recommendations to accelerate infrastructure investment and regulatory enforcement, thereby advancing sustainable development in Libya's hydrocarbon sector.